Apparent metabolizable energy of cereal grains for broiler chickens is influenced by age - Khalil, M.M. (Poult Sci, 2021)
The current study was conducted to investigate the influence of broiler age on the AME and AMEn of 4 common cereal grains (wheat, sorghum, barley, and corn). Four experimental diets with the same inclusion (962 g/kg) of each grain were developed and fed to groups of broiler chickens aged 1 to 7, 8 to 14, 15 to 21, 22 to 28, 29 to 35, or 36 to 42 d post-hatch. Each diet, in pellet form, was randomly allocated to 6 replicate cages in each age group. Except for the 0 to 7 d age group, the birds were fed a starter (d 0–21) and/or a finisher (d 21–35) diet before the introduction of experimental diets. The number of birds per cage were 10 (d 1–7) and 8 (d 8–42). Excreta were collected over the last 4 d of each age period. The AME and AMEn of the grains were determined by the total excreta collection. Bird age influenced (P < 0.001) the AME and AMEn of all cereal grains. The AMEn of wheat declined quadratically (P < 0.01) with advancing age, from 3,461 kcal/kg in wk 1 to 3,219 kcal/kg in wk 2 and then plateaued. The AMEn of sorghum grain declined linearly (P < 0.001) with advancing age, from 3,762 kcal/kg in wk 1 to 3,614 kcal/kg in wk 2, plateaued to wk 5 and then declined to 3,556 kcal/kg in wk 6. A quadratic (P < 0.001) reduction in the AMEn of barley was observed as birds grew older, with the AMEn decreasing between wk 1 (3,286 kcal/kg) and wk 2 (2,988 kcal/kg), increasing in wk 3 (3,117 kcal/kg) and then plateauing. The AMEn of corn declined quadratically (P < 0.05) with advancing broiler age; the highest AMEn was observed in wk 1 and 5, the lowest AMEn in wk 2, with the other weeks being intermediate. In conclusion, the present results showed that broiler age has a substantial impact on the AME and AMEn of cereal grains and the effect varied depending on the cereal grain. These data suggest that age dependent AME and AMEn values may need to be considered when formulating broiler diets to improve the precision of feed formulation and production efficiency.